Degradation and biocompatibility of photoembossed PLGA–acrylate blend for improved cell adhesion. Issue 1 (2nd December 2016) - Hughes‐Brittain, Nanayaa F.; Qiu, Lin; Wang, Wen; Peijs, Ton; Bastiaansen, Cees W. M.
Abstract: We have shown previously that PMMA–acrylate photopolymers are biocomopatible and can exhibit improved cell adhesion compared to PMMA, due to an increase in negative surface charge caused by UV radiation PLGA has been used widely in soft tissue regeneration due to its high biocompatibility and cell adhesion. This polymer is also biodegradable and can be utilised in the field of vascular regeneration. In this study, PLGA is blended with a triacrylate monomer (TPETA) to create a degradable photopolymer blend. Surface relief structures are formed on this PLGA–TPETA by photoembossing. An optimum height of 950 nm was achieved for a 10 µm pitch with the height of these relief structures being controlled by changing UV intensity, processing temperature and time. Degradation studies of this blend revealed a bulk degradation mechanism with PLGA–TPETA degrading slower compared to pure PLGA. We also evaluated the adhesion of human umbilical vein endothelial cells (HUVECs) on both smooth and textured PLGA–TPETA films. Embossed PLGA–TPETA films showed improved cell adhesion compared to smooth substrates. Furthermore, HUVECs proliferated faster on the embossed surface compared to their smooth counterparts. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 163–171, 2018.